Data mining approach in determining the relationships between the economy and the general government sector - Tomasz Skica; Jacek Rodzinka; Teresa Mroczek (e-Finanse: Financial Internet Quarterly, 2015)
This article is dedicated to a study of the relations between the economy and the size of the general government sector. The main aim of the article is an identification of the most important variables that are used to determine relations between the economy and size of the sector, as well as to identify frequency of their occurrences in relations to pairs of variables which describe an economy and the size of the sector. In order to explore these relations, the authors used Bayes networks. The economies of EU member states and their public finance systems were the object of analyses in this article. The period that was selected for the research covered the years 2000-2013 (inclusive). In order to describe economies, the authors selected 18 variables, whereas to describe the general government sector - 15 variables. These variables were sourced from databases of Eurostat, OECD and the World Bank. Among an economy's measures and general government sector measures, there were also some benchmarks found (standard and classic) as well as measures proposed by the authors, which had not been used in the scientific descriptions that were dedicated to research on size of the general government sector. Ipso facto, this article fits in the discussion on not only the size of the general government sector, but also attempts to answer the question of whether the economy determines the size of the sector. To date, the research questions on the impact of the size of the general government sector on the economy of a particular country have been common. This article inverts the investigated dependence and its content concentrates on the attempt to determine if the size of the sector in a particular country is a function of its economy expressed by ratios adopted in conducted the research.
Keywords: E62; H11; H20; H50; H60; 330; economy; central government; general government sector; economy; public finance; relationship between economy and general government sector size